Perímetro e área: análise de pesquisas sob a ótica da teoria dos registros de representação semiótica - Miranda, Steffani Maiara Colaço (2018)
The main objective of this research is to understand how the teaching of perimeter and area have been working from the point of view of the Theory of Semiotic Representation Registers and eventual adaptation to the teaching of the deaf. The objectives were: to select studies of perimeter and area in the pertinent bibliography for both for hearing and deaf students; analyze the tasks proposed on these studies, from the theoretical point of view taken.This research is characterized as a bibliographical research,from dissertations and theses analyzed geometry tasks applied to hearing and deaf students. For analysis of the tasks was taken as reference analysis developed by another researcher, with geometry content. As results, were identified that most of the tasks developed required the mereological modification and required the inventor's vision. It was verified that there was no difference between the tasks for deaf students or listeners, only the use of manipulatives, such as Tangram, was important in the works with deaf students.